The peculiarities of the methods of PE classes using the elements of the taekwon do. - Gavrilyk V.O (Kharkov National Pedagogical University, 2011)
heoretical and methodological aspects of the methods of PE classes using the elements of the taekwon-do do of innovated technologies in education in the sphere of physical education and sport have been examined. In research took part 112 pupils of 8-9 classes. It is defined that introduction in educational process elements of martial arts will have an impact on locomotor apparatus, vascular and respiratory systems of an organism.